Simulator-Based Training in FoCUS with Skill-Based Metrics for Feedback: An Efficacy Study - Robert Morgan; Bradley Sanville; Shashank Bathula; Shaban Demirel; Serene Perkins; Gordon E. Johnson (POCUS Journal, 2019)
Introduction: Focused Cardiac Ultrasound (FoCUS) is a relatively new technology that requires training and mentoring. The use of a FoCUS simulator is a novel training method that may prompt greater adoption of this technology by physicians at different levels of training and experience. The objective of this study was to determine if simulation training using an advanced echo simulator (Real Ultrasound®) is a feasible means of delivering training in FoCUS. Methods: Twenty-five residents and attending physicians participated in this study. After performing a pretest, training on the Real Ultrasound® was administered. Improvement was assessed immediately after simulator training. Additionally, some participants were retested six months after training to determine whether learned skills were retained. Results: Of the 25 participants recruited, all completed the pretest phase, and 17 completed the training and immediate posttest assessment. At pretest, the median angular deviation of acquired images from anatomically correct was 37°, which improved to 30° after training (p<0.002). Technical skill was largely maintained at six months of follow-up, with a median angle error of 27 and 31°, respectively (p=0.093) in 8 participants who completed the post and six-month retention assessments. The median pretest image interpretation score improved from 55% to 70% (p=0.028); median post and six month scores in the 8 participants were 72 and 68%, respectively (p=0.735). Conclusions: Simulation training in FoCUS significantly improves skills in image acquisition. These skills appear to be retained over time. This study adds support for the use of advanced echocardiographic simulators to enhance formal FoCUS training in a real-world setting.